Listen to medieval women through procedural documentation (Catalan processes of the 14th and 15th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
We present some notes about work, freedom and female solidarity in the 14th and 15th centuries, based on the words collected in the procedural documentation from several archives of Barcelona. More than the facts, the circumstances and the outcome of the trials, we are interested in what they did, how they reacted, what the women thought. When authorities ask witnesses about an incident, they always tell us what they were doing when it happened, so they offer us real pictures of women everyday life. When they ask the complainants, or the accused, they tell us about their anxieties, their problems. We have divided our contribution into two parts, first we give a vision of women's jobs and their daily lives in the city of Barcelona. In the second part we study statements of two diametrically different women, a free woman of Greek origin, violently removed from Barcelona, and a noble lady attacked in the castle she rules, located in the Pyrenees. In both cases we can talk about freedom and also solidarity. Let's listen to their voices.
Keywords: Judicial processes; women's jobs; freedom; solidarity; Barcelona; Pallars county